2022
DOI: 10.1002/aelm.202200918
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐second Lifetime of Photocarriers in Hybrid Lead Halide Perovskite

Abstract: Recently lead halide perovskite based solar cells have rapidly advanced and their power conversion efficiency (PCE) increased to 25.7%. The progress has been attributed to the super‐long carriers’ lifetime (τ) and long diffusion length (LD) of the photocarriers, however it has been a challenge to precisely characterize and understand the super‐long τ and LD of photocarriers. Here, a MAPbI3 single crystal exhibits four different τ which increase with LD extending from nm scale to mm scale. The prior two lifetim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Multifunctional photodetectors (MPDs) based on semiconductor photoconductive and/or photovoltaic effects have received significant attention in recent years due to their dominance in space exploration, encrypted communication, and biomedical directional detection. The position-sensitive detectors (PSDs) based on the lateral photovoltaic (LPV) effect are a special type of PDs that can be used for the position detection of a light beam. In this context, the pivotal parameters defining PDs are their position sensitivity and relaxation time. Self-powered ultraviolet MPDs based on SiC Schottky or p – n junctions have several advantages, including small size, high-speed operation, and excellent stability in harsh environments. The position sensitivity of 67.8 mV/mm with a relaxation time of 30 μs had been observed in Fe 3 O 4 /3C-SiC Schottky junctions, but the long relaxation time restricts their practical applications . Liu et al observed a large position sensitivity (750.86 mV/mm) and ultrafast relaxation time (0.49 μs) in a triple-layer Ga 2 O 3 /NiO/SiC heterojunction, suggesting the importance of the built-in electric field in the junction for high-performance PSDs .…”
Section: Introductionmentioning
confidence: 99%
“…Multifunctional photodetectors (MPDs) based on semiconductor photoconductive and/or photovoltaic effects have received significant attention in recent years due to their dominance in space exploration, encrypted communication, and biomedical directional detection. The position-sensitive detectors (PSDs) based on the lateral photovoltaic (LPV) effect are a special type of PDs that can be used for the position detection of a light beam. In this context, the pivotal parameters defining PDs are their position sensitivity and relaxation time. Self-powered ultraviolet MPDs based on SiC Schottky or p – n junctions have several advantages, including small size, high-speed operation, and excellent stability in harsh environments. The position sensitivity of 67.8 mV/mm with a relaxation time of 30 μs had been observed in Fe 3 O 4 /3C-SiC Schottky junctions, but the long relaxation time restricts their practical applications . Liu et al observed a large position sensitivity (750.86 mV/mm) and ultrafast relaxation time (0.49 μs) in a triple-layer Ga 2 O 3 /NiO/SiC heterojunction, suggesting the importance of the built-in electric field in the junction for high-performance PSDs .…”
Section: Introductionmentioning
confidence: 99%